Implications of mRNA-based SARS-CoV-2 vaccination for cancer patients - Emanuela Romano; Patrick Ott; Steve Pascolo (Journal for ImmunoTherapy of Cancer)
SARS-CoV-2 infection and the resulting COVID-19 have afflicted millions of people in an ongoing worldwide pandemic. Safe and effective vaccination is needed urgently to protect not only the general population but also vulnerable subjects such as patients with cancer. Currently approved mRNA-based SARS-CoV-2 vaccines seem suitable for patients with cancer based on their mode of action, efficacy, and favorable safety profile reported in the general population. Here, we provide an overview of mRNA-based vaccines including their safety and efficacy. Extrapolating from insights gained from a different preventable viral infection, we review existing data on immunity against influenza A and B vaccines in patients with cancer. Finally, we discuss COVID-19 vaccination in light of the challenges specific to patients with cancer, such as factors that may hinder protective SARS-CoV-2 immune responses in the context of compromised immunity and the use of immune-suppressive or immune-modulating drugs.